2018
DOI: 10.1186/s12884-018-1725-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel motivational interviewing (MI) informed peer-support intervention to support mothers to breastfeed for longer

Abstract: BackgroundMany women in the UK stop breastfeeding before they would like to, and earlier than is recommended by the World Health Organization (WHO). Given the potential health benefits for mother and baby, new ways of supporting women to breastfeed for longer are required. The purpose of this study was to develop and characterise a novel Motivational Interviewing (MI) informed breastfeeding peer-support intervention.MethodsQualitative interviews with health professionals and service providers (n = 14), and foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…For example, Trickey et al [29] and the recent multicentre RUBY (Ringing Up about Breastfeeding Early) trial undertaken in Australia found that repeated contacts in the early postnatal period (a risk period for discontinuation), and proactive support, created important opportunities for breastfeeding support [52]. Furthermore, our findings emphasise how emotionally warm and enabling relationship with the peer support enhanced women’s motivation, similar to the elements of emotional accessibility identified by Trickey et al [29] and others [35, 51]. Our findings support wider literature that emphasises the need for multiple opportunities for women to access support for infant feeding [13, 16].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For example, Trickey et al [29] and the recent multicentre RUBY (Ringing Up about Breastfeeding Early) trial undertaken in Australia found that repeated contacts in the early postnatal period (a risk period for discontinuation), and proactive support, created important opportunities for breastfeeding support [52]. Furthermore, our findings emphasise how emotionally warm and enabling relationship with the peer support enhanced women’s motivation, similar to the elements of emotional accessibility identified by Trickey et al [29] and others [35, 51]. Our findings support wider literature that emphasises the need for multiple opportunities for women to access support for infant feeding [13, 16].…”
Section: Discussionsupporting
confidence: 82%
“…More simply, this model enables intervention designers to consider a) ‘what behaviours do I want to target?’ (inner layer), b) ‘how am I going to change the behaviour and what elements does the intervention need?’ (second layer), and c) ‘what needs to be in place for the intervention to be delivered?’ (outer layer). The COM-B model has been used to inform and evaluate complex interventions such as a tobacco control strategy [33] and obesity strategy [34] and to develop a motivational interviewing based breastfeeding peer support intervention [35].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growth in research using the COM-B to undertake a behavioural analysis in a range of behaviours [17][18][19][20]. Fewer studies have undertaken the full BCW process to design and test an intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should be focused on the development and the evaluation of breastfeeding community support programmes which aim to enhance maternal breastfeeding self-e cacy. These programmes could include both formal and peer mother-tomother support groups [57][58][59]. A number of intervention studies have been designed based on self-e cacy theory and/or investigated the effect of breastfeeding education and/or support programmes explicitly through the enhancement of self-e cacy.…”
Section: Implications For Research and Practicementioning
confidence: 99%